Design optimisation of multi-stream plate fin heat exchangers with multiple fin types. (25th February 2018) - Guo, Kunpeng; Zhang, Nan; Smith, Robin
Highlights: Mix-and-match fin types concept is proposed and applied in the design methodology. Continuous heat transfer and pressure drop expressions simplify MINLP to NLP. Case study validate and demonstrate the effectiveness of new design methodology. Abstract: For multi-stream plate fin heat exchanger design, one needs to consider the optimal combination of fin categories and detailed geometries of fin types. Due to the complexity of the design problem for multi-stream plate fin heat exchangers, a major limitation of existing technology is the lack of a general design methodology that can consider mix-and-match fin type selection and imposed constraints simultaneously to take advantage of different fin characteristics. In this work, a new design method is proposed to consider the possibility of mix-and-match fin types. Multi-stream plate fin heat exchangers with mix-and-match fin types is considered as a network of two-stream plate fin heat exchangers. A mixed integer nonlinear programming (MINLP) model is converted into a nonlinear programming (NLP) model, and solved in combination of enumeration for a few remaining binary variables. The objective is to minimise the total capital cost. Case studies are carried out to validate the effectiveness of new proposed design methodology and demonstrate the benefits of mix-and-match fin type combinations in the overall design methodology.